المكان السلبي ودلالات الفناء في رواية ئاسوس ل (محيي الدين زنگنه) - احمد, تارا اسماعيل; البرزنجي, اسماعيل ابراهيم مصطفى (Sulaimani Journal for Humanities, 2021)
This novel refers to one of the most important phases of the Kurds struggle. The events are about a family which depicts the Kurds as whole. The suffering of the family is the same as the suffering of the Kurdish race. Throughout the novel, the struggle of the Kurds are illustrated symbolically. There is no doubt that the chosen style of writing of this novel, symbolic writing, is the result of the critical period in which the novelist wrote it, which was during the former Iraqi regimes’ pressure. Therefore, the researcher choose a semiotic method to find some indicators. This is to attain the conveyed meaning behind the narration of Asos Novel. This novel represents the Kurdish society and helps the readers to comprehend this community. It also shows the culture and traditions. By this method, semiotics, Kurdish culture and tradition can be introduced to the Arabic society. Time, places, characters and events of the novel are symbols represented from the writer to the readers. The role of the reader is to dismantle those symbols to comprehend and attain the real message that the author wants to send. The events of the novel might express what the writer had been through in his life. He writes about events personal to him, however, he could not have referred to them directly due to the oppression of the ruling authority. Thus, he portrays the events through symbols. This study concentrates on the negative places in the novel such as prisons, hospitals, cages etc. Sometimes, the places are positive while the characters are negative. For example, the house becomes prison for Farhad because of his outcast. We have discussed negative places with a semiotic approach in two subtle ways. First, we explored hostile places. Second, we discussed enclosed places.